Development Of Explosion Box Media Recognizing Culinary Heritage - Nurjanah, Nunung; Firyal, Fadila Fikri; Saputri, Anggi Martiningtyas Januwati; Effendi, Muhammad Idris (JURNAL DIMENSI PENDIDIKAN DAN PEMBELAJARAN, 2025)
The objectives of this research: 1) produce a product in the form of explosion box media; 2) analyze the suitability of the explosion box media; 3) analyze the effectiveness of the explosion box media. This Development Research or RD uses Sugiyono's development model, the stages it goes through include: 1. potential and problems; 2. data collection; 3. product design; 4.design validation; 5. design revision; 6. product testing, and 7. product revision. The research subjects were media experts and material experts who acted as validators, as well as language experts, with one expert each and 30 respondents aged between 7 and 13 years who lived in Kampoeng Heritage Kajoetangan Malang. Data collection uses questionnaires and assessment sheets from material experts, language experts and media experts to evaluate how effective the explosion box media is. Produce: 1) explosion box media getting to know the Kampoeng Heritage Culinary of Kajoetangan Malang; 2) the explosion box media recognizes that the Kampoeng Heritage Kajoetangan Malang Culinary is suitable for use, this is in accordance with the results of validation by material experts who gave a score of 87.5%, media experts 88.6%, and language experts 84.3%; 3.) shows the effectiveness of the explosion box media to get to know the culinary delights of Kampoeng Heritage Kajoetangan Malang which was tested using a validity test and a reliability test which showed a result of 0.755 which means reliable.